The Legal Framework of Advocacy Planning in Territorial Splitting: How is civil society involved in shaping local policies? - Diki Suherman; Ridwan Sutriadi; Adenantera Dwicaksono; Tommy Firman; Sarbini Sarbini (Khazanah Hukum, 2025)
In Indonesia, the process of territorial splitting, where regions are divided to form new autonomous areas, has been a significant aspect of local governance, particularly in the context of decentralization. The legal framework for territorial splitting is outlined in Law No. 23 of 2014 on regional government, which serves as the constitutional basis for decentralization principles in implementing territorial splitting. This study aims to explore in depth the legal framework and the opportunities and challenges in territorial splitting to improve governance, address regional disparities, and enhance public service accessibility at the local level in Pangandaran Regency, Indonesia. The case study of Pangandaran Regency illustrates a strong legal framework and the efforts of various actors, including civil society groups, political parties, and regional leaders, working together to influence decision-making and policy formation. This research adopts a mixed-methods approach, predominantly qualitative in nature, to analyze the content of regulations governing territorial splitting and explore the role of civil society in the advocacy planning process of territorial splitting in Indonesia. The study focuses on Pangandaran Regency, utilizing Social Network Analysis (SNA) to map and analyze the relationships between key actors, such as civil society groups, political parties, and local leaders, involved in advocating for regional autonomy to uncover the dynamics between these actors, revealing how they form coalitions to advocate for regional autonomy. These advocacy efforts are closely aligned with the United Nations Sustainable Development Goals (SDGs), particularly Goal 16, which promotes peace, justice, and strong institutions by fostering inclusive and participatory decision-making. Through strong and clear legal standing and coordinated advocacy, civil society and political actors successfully push for the establishment of new autonomous regions, such as Pangandaran. This not only enhances local governance but also fosters economic development and reduces regional disparities. By highlighting the role of civil society in policy-making, this study sheds light on how advocacy planning can drive sustainable development and better governance in Indonesia’s evolving decentralization landscape.